2019
DOI: 10.1002/jtr.2339
|View full text |Cite
|
Sign up to set email alerts
|

Tourists' emotional changes and eWOM behavior on social media and integrated tourism websites

Abstract: Electronic word of mouth (eWOM) has become increasingly important for the tourism industry. However, existing studies tend to overlook tourists' eWOM sharing behavior, especially on different platforms. This paper aims to explore the antecedents of distinct eWOM behaviors on social media platforms and integrated tourism websites. Thirty tourists with rich travel experience were invited to attend in-depth interviews. Tourists' emotions, eWOM motivations, and platform features were explored by coding. Based on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 60 publications
1
32
1
Order By: Relevance
“…Positive hospital brand image would result in positive decision outcome towards the hospital. Thus, this brand image formation implies the importance of marketing communication in the pre‐service consumption stage (Cham et al, 2020; Zhou et al, 2020). Advertisements with rich contents and persuasive power can effectively deliver informative messages to potential customers.…”
Section: Discussion and Implications Of Research Findingsmentioning
confidence: 99%
“…Positive hospital brand image would result in positive decision outcome towards the hospital. Thus, this brand image formation implies the importance of marketing communication in the pre‐service consumption stage (Cham et al, 2020; Zhou et al, 2020). Advertisements with rich contents and persuasive power can effectively deliver informative messages to potential customers.…”
Section: Discussion and Implications Of Research Findingsmentioning
confidence: 99%
“…This communication is defined as the evaluation, comments, recommendations, and opinions developed online by users and consumers [66,100]. In addition, young consumers rely more on eWOM communication than on face-to-face communication or official online information from the provider [101][102][103]. Therefore, the second hypothesis states that: Hypothesis 2 (H2).…”
Section: The Effect Of Ewom Communication On the Perceived Quality Of Information About Products And Servicementioning
confidence: 99%
“…Tourism and Hospitality industry is a pioneer in using online platforms and eWOM and the importance of eWOM in this industry has been extensively overstated by both researchers and practitioners (Cantallops & Salvi, 2014;Zhou et al, 2020;Zsarnoczky, 2018). Tourism platforms that provides eWOM such as TripAdvisor facilitate sharing knowledge, experiments, emotions toward resorts and tourism destinations (Zhou et al, 2020).…”
Section: Electronic Word Of Mouth (Ewom) Toward Resortsmentioning
confidence: 99%
“…Tourism and Hospitality industry is a pioneer in using online platforms and eWOM and the importance of eWOM in this industry has been extensively overstated by both researchers and practitioners (Cantallops & Salvi, 2014;Zhou et al, 2020;Zsarnoczky, 2018). Tourism platforms that provides eWOM such as TripAdvisor facilitate sharing knowledge, experiments, emotions toward resorts and tourism destinations (Zhou et al, 2020). Previous researches have revealed that satisfied customers show positive emotions and spread positive detailed eWOM in online platforms about their experience at a particular hotel which show their gratitude and possibly lead to loyalty (Han et al, 2018) and vice versa (Verhagen et al, 2013).…”
Section: Electronic Word Of Mouth (Ewom) Toward Resortsmentioning
confidence: 99%